Empowering Women Farmers through the Moengko Nursery House Program in Poso District - Putra, Achmad Budiawan; Rahman, Fahmi Khatib; Suheri Sastri, Muhammad; Saswini, Andi Ade Ula (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
The farmer mother’s empowerment program is a very important and strategic initiative in an effort to improve the welfare of rural communities. This program aims to empower farmer mothers in Poso through the implementation of the Moengko Nursery House Program, a collaborative initiative between PT Pertamina Patra Niaga Fuel Terminal Poso and the local community. The program is focused on improving the skills and capacity of farmer mothers in crop cultivation, particularly through the development of sustainable nursery houses. The methods used in this program include technical training, field assistance, cooperative system education, and the Moengko healthy kitchen program. The location of the Moengko Nursery House Program activities is located in Poso Terminal Fuel operational area. The target of this program is the Citra Bersatu Women Farmers Group, which consists of 12 people in Moengko Village. The results of this activity showed an increase in the knowledge and skills of farm women in cultivation techniques, including the selection of superior seeds, seeding techniques, and plant care. In addition, the program also succeeded in establishing a cooperative system that encourages the sustainability of farmer group businesses, as well as the promotion of the Moengko Healthy Kitchen Program. The program evaluation showed a positive impact on the independence of farmer mothers in procuring vegetables independently, the cooperative system of vegetable cultivation, and the processing of healthy food ingredients for the family.